RUNWAY PCN DESIGN THROUGH SEVERAL CPT CORRELATION WITH FAARFIELD - Sandy Radhitya Akbar; Monika Sutarsa; Nuuri Anjani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Several places need a pioneer airport in several area. However it doesnot close the probability that sometimes the bigger airship needs a bigger quality. For an instance the pioneer airport use only a thin runway layer, when it need to be upgraded some of them destroy an existing layer and create a new one. In order to save more money in airship runway design we need to maximize thickness layer based on potentially next served airship.